1997
DOI: 10.1172/jci119806
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 promotes activation-induced cell death of SLE lymphocytes mediated by Fas ligand.

Abstract: Immune function in SLE is paradoxically characterized by active T cell help for autoantibody production, along with impaired T cell proliferative and cytokine responses in vitro. To reconcile these observations, we investigated the possibility that the accelerated spontaneous cell death of SLE lymphocytes in vitro is caused by an activation-induced cell death process initiated in vivo. 27 SLE patients, three patients with systemic vasculitis, seven patients with arthritis, and 14 healthy subjects were studied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
108
0
1

Year Published

2000
2000
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(116 citation statements)
references
References 67 publications
(52 reference statements)
7
108
0
1
Order By: Relevance
“…Spontaneous T cell apoptosis was not statistically different between EPEPϩ/ϩ, EPEPϩ/Ϫ, and EPEPϪ/Ϫ individuals among either SLE patients or healthy controls. Several investigators have reported the analysis of spontaneous T cell apoptosis in patients with SLE (36)(37)(38). Spontaneous apoptosis immediately after isolation of T cells from SLE patients (regardless of their level of disease activity) was not significantly increased compared with that of T cells from healthy controls (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous T cell apoptosis was not statistically different between EPEPϩ/ϩ, EPEPϩ/Ϫ, and EPEPϪ/Ϫ individuals among either SLE patients or healthy controls. Several investigators have reported the analysis of spontaneous T cell apoptosis in patients with SLE (36)(37)(38). Spontaneous apoptosis immediately after isolation of T cells from SLE patients (regardless of their level of disease activity) was not significantly increased compared with that of T cells from healthy controls (37).…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have reported the analysis of spontaneous T cell apoptosis in patients with SLE (36)(37)(38). Spontaneous apoptosis immediately after isolation of T cells from SLE patients (regardless of their level of disease activity) was not significantly increased compared with that of T cells from healthy controls (37). When cultured for several days, T cells from SLE patients showed significantly increased apoptosis compared with those obtained from controls.…”
Section: Discussionmentioning
confidence: 99%
“…In lpr and gld mice, defects in PCD signaling through the Fas pathway appear to predispose to autoimmunity [29]. Whereas mutations of the Fas receptor (FasR) or Fas ligand (FasL) have been associated with a lupus-like autoimmune syndrome in mice with the lpr or gld genetic background [29], Fas-mediated signaling appears to be intact in human SLE [30]. Lupus T cells demonstrate defective activation-induced cell death (AICD) [31].…”
Section: Mhp Increased Roi Production Cytoplasmic Alkalinization Anmentioning
confidence: 99%
“…Cell-surface expression of FasR [39] and FasL is also redox sensitive [40]. Increased ROI levels might be related to increased IL-10 production, release of FasL and overexpression of FasR in SLE [30]. Elevated NO production might also contribute to increased spontaneous apoptosis [41].…”
Section: Mhp Increased Roi Production Cytoplasmic Alkalinization Anmentioning
confidence: 99%
“…The established facts are that (i) IL-10 favors the maturation of TH2 lymphocytes; (ii) IL-10 prevents tumour antigen presentation to CD8ϩ CTLs by suppressing the expression of MHC class I and II antigens; 31,32 and (iii) in certain clinical conditions, IL-10 may regulate the survival or death of immune cells via the CD95/ CD95L (Fas/Fas-L)-dependent apoptotic pathways. 33,34 It has been demonstrated that IL-10 induces apoptosis not only in CD4ϩ lymphocytes and NK cells [33][34][35] but also in human monocytes. 36 All these immune cells are of central importance in the initiation, development and outcome of the immune response.…”
Section: Il-10 Cytokine Gene Polymorphisms In Different Stages and Dementioning
confidence: 99%